Female sovereignty in the «kingdom of Tendre» of Madeleine de Scudéry (El Hilo de la Fabula, 2025)
In 17th-century France, women of the elite class asserted their power and established themselves as influential figures, thus challenging the limitations of subordination imposed by the culture of the time. To illustrate this, we will examine the work of the writer and moralist Madeleine de Scudéry, who, following in the footsteps of Christine de Pizan's The Book of the City of Ladies, describes heroic and strong women in her novel Clélie, histoire romaine. Furthermore, she included ‘The Map of Tendre’, an allegorical map of friendship, which, not without criticism, introduced a new symbolic framework that, from a woman's perspective, explained the various stages men had to overcome, both in fiction and in reality, to be recognized as worthy members of her ‘kingdom’ and, thus, become the ideal «honorable man».
Keywords: French literature; Scudéry; Clélie; Tendre; sovereignty; women